Reactor criticals and spent fuel systems similarities - Matěj Šikl (Acta Polytechnica CTU Proceedings, 2022)
Many conservative assumptions for subcriticality assessment calculations have to be made in current calculations of spent fuel storage systems. This is due to a fact that there is no available database of benchmarks containing spent fuel or materials with isotopic composition like spent fuel. However one potential source of spent fuel system experiments is being omitted – there are hundreds of commercial reactors around the world containing spent fuel on some level of burnup. These reactors have to be tested for safety reasons in the beginning of each cycle and parameters of these test states are well known. In this paper a possibility of using commercial reactor critical states for code validations and for subcriticality assessments of storage systems is discussed and potential approach for criticality safety analysis is given.